2020
DOI: 10.1177/1524839920904688
|View full text |Cite
|
Sign up to set email alerts
|

Nudging Urban Food Pantry Users in Utah Toward Healthier Choices

Abstract: Purpose. To evaluate the impact of a nudge program on food pantry clients’ self-reported selection and use of healthy foods. Method. A convenience sample of clients of six urban food pantries in Utah were surveyed about their experience with the Thumbs Up for Healthy Choices nudge program. Chi-square tests were used to identify associations between demographic characteristics and self-reported program impact. Results. Ninety-four percent (n = 158) of respondents agreed that the program made it easier to make h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Behavioral economics is the “study of social, cognitive, and emotional factorswhich aims to understand and influence economic decisions or purchasing behaviors” [ 25 ] (p. 4). Changes based on behavioral economics have been shown to increase the selection of targeted food items in experimental and real-life settings including food pantries [ 25 , 26 , 27 , 28 , 29 ]. The HFE intervention aimed to promote access to and appeal of healthy, lower-sodium items by encouraging pantries to employ strategies, such as: increasing the visibility or convenience of the items; placement of such items early or repeatedly in the shopping experience; use of signage, recipes, cooking demonstrations, or nutrition information to highlight the items; communicating the normalcy or popularity of such items; and bundling such items with other ingredients to promote selection.…”
Section: Methodsmentioning
confidence: 99%
“…Behavioral economics is the “study of social, cognitive, and emotional factorswhich aims to understand and influence economic decisions or purchasing behaviors” [ 25 ] (p. 4). Changes based on behavioral economics have been shown to increase the selection of targeted food items in experimental and real-life settings including food pantries [ 25 , 26 , 27 , 28 , 29 ]. The HFE intervention aimed to promote access to and appeal of healthy, lower-sodium items by encouraging pantries to employ strategies, such as: increasing the visibility or convenience of the items; placement of such items early or repeatedly in the shopping experience; use of signage, recipes, cooking demonstrations, or nutrition information to highlight the items; communicating the normalcy or popularity of such items; and bundling such items with other ingredients to promote selection.…”
Section: Methodsmentioning
confidence: 99%
“…These nudges successfully applied the convenience and attractiveness aspects of the "CAN" approach to increase patrons' selection of targeted foods. Another study evaluated changing shelf signage and posters in urban food pantries in Utah (10). Highly visible shelf labels with colorful "thumbs up" images that said "Healthy Choice" in English or Spanish were placed under targeted healthy foods, and bilingual posters were displayed in the pantry to raise awareness about the shelf tags and target foods.…”
Section: Food Pantriesmentioning
confidence: 99%
“…Also, these studies tend to rely heavily on self-reported and observational data, thus, more standardized and objective measurements of changes in diet quality in lowincome food pantry patrons are also needed (20). Additionally, given potential differences in food choices attributable to cultural preferences (10), future research is needed to better understand how cultural appropriateness can be incorporated into choice architecture across diverse populations.…”
Section: Food Pantriesmentioning
confidence: 99%
See 2 more Smart Citations